2010
DOI: 10.1007/s00432-010-0838-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cyfra 21.1 and galectin-3 protein levels in relation to immunohistochemical cytokeratin 19 and galectin-3 expression in patients with thyroid tumors

Abstract: While CK19 and gal-3 are accurate as tissue markers, their serum levels could not be used as reliable markers for identification of thyroid malignancy or in thyroid cancer follow-up. On the other hand, a tendency toward higher serum levels of Cyfra 21.1 in the small number of PDTC patients examined adds weight to previous reports postulating a role for cytokeratins in predicting a high degree of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 40 publications
1
25
0
1
Order By: Relevance
“…In our series, patients with 131 I-refractory metastases had significantly higher Cyfra 21.1 levels than patients with 131 I-avid ones. This conforms with previous data as increased Cyfra 21.1 levels were found in patients with primary aggressive DTC but not primary and metastatic classical DTC histotypes (16,17,21). Such differences argue that 131 I-refractory thyroid cancer cells (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…In our series, patients with 131 I-refractory metastases had significantly higher Cyfra 21.1 levels than patients with 131 I-avid ones. This conforms with previous data as increased Cyfra 21.1 levels were found in patients with primary aggressive DTC but not primary and metastatic classical DTC histotypes (16,17,21). Such differences argue that 131 I-refractory thyroid cancer cells (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have revealed an elevated concentration of serum galectin-3 in various cancers, including breast (20), colorectal (21,22), stomach (23), lung (20), bladder (24), head and neck (25), liver (26), thyroid (27), pancreatic (28) and melanoma (29). These studies demonstrated higher amounts of galectin-3 in the sera of patients and its association with poorer prognosis.…”
Section: Introductionmentioning
confidence: 80%
“…Accumulating evidences have revealed an elevated concentration of serum galectin-3 in various cancers including breast 16) , colorectal 17,18) , stomach 19) , lung 16) , bladder 20) , head and neck 21) , liver 22) , melanoma 23) , pancreatic 24) , and thyroid [25][26][27][28][29] . As for thyroid cancer, Yılmaz et al reported that serum galectin-3 level was a significant biomarker to distinguish thyroid cancer from benign nodules 25) .…”
Section: Introductionmentioning
confidence: 99%
“…As for thyroid cancer, Yılmaz et al reported that serum galectin-3 level was a significant biomarker to distinguish thyroid cancer from benign nodules 25) . However, the significance of circulating galectin-3 as a biomarker is still controversial [26][27][28][29] . Recently, Chen et al reported that galectin-3 induces secretion of metastasis-promoting cytokines, such as interleukin (IL)-6, granulocyte colony-stimulating factor Circulating galectin-3 correlates with angiogenetic factors, indicators of nutritional condition and systemic inflammation in patients with thyroid cancer Tatsuo Shimura 1) , Masahiko Shibata 2) , Kenji Gonda 2) , Takahiro Nakajima 3) , Shun Chida 3) , Masaru Noda 3) , Satoshi Suzuki 4) , Izumi Nakamura 4) , Keiichi Nakano 4) , Toshihiko Fukushima 4) , Shinichi Suzuki 4) (G-CSF), granulocyte macrophage colony-stimulating factor and soluble intercellular adhesion molecule-1 (sICAM-1) 30) .…”
Section: Introductionmentioning
confidence: 99%